Ultrasonography aspects, biometry and Doppler of howler monkey (Alouatta fusca) ocular bulb Aspectos ultrassonográficos, biometria e dopplerfluxometria ocular do bugio ruivo (Alouatta fusca) - Souza L.P.* (2018)
© 2018 Colegio Brasileiro de Patologia Animal.This study aimed to describe the sonographic features of normal ocular structures, the ocular biometry and Doppler parameters of the internal ophthalmic artery and central retinal artery of the Alouatta fusca. Twenty ocular ultrasonographic examinations were perform in ten primate species of the Alouatta fusca. Proceeded to the sonographic description of the ocular structures and later biometrics was obtained in four distances: (D1) corresponding to the anterior chamber (D2) lens thickness (D3) vitreous chamber and (D4) axial length of the eyeball. Doppler ultrasound evaluated internal ophthalmic artery and central retinal artery as for the resistivity Index (RI), pulsatility index (PI), peak systolic velocity (PSV) and end diastolic velocity (EDV). The values of biometrics and flowmetry underwent comparison test between genders and sonographic views, by Student t test. The anatomical sonographic description of the ocular structures and vasculature of the red howler were similar to species such as dog, cat and man. The biometric average values found were 2.1±0.38mm for D1, 3.7±0.30mm for D2, 10.4±0.78mm for D3 and 19.3±1.64mm for D4. The Doppler values of the ophthalmic artery and central retinal artery found were: PSV of 25.6cm/s and 14.6cm/s; VDF 15.8cm/s and 10.7cm/s; IR 0.7 and 0.5; IP 1.4 and 0.8.